The Th17/IL-17 Axis and Kidney Diseases, With Focus on Lupus Nephritis - Paquissi, Feliciano Chanana; Abensur, Hugo (Frontiers in Medicine, 2021)
Systemic lupus erythematosus (SLE) is a disease characterized by dysregulation and hyperreactivity of the immune response at various levels, including hyperactivation of effector cell subtypes, autoantibodies production, immune complex formation, and deposition in tissues. The consequences of hyperreactivity to the self are systemic and local inflammation and tissue damage in multiple organs. Lupus nephritis (LN) is one of the most worrying manifestations of SLE, and most patients have this involvement at some point in the course of the disease. Among the effector cells involved, the Th17, a subtype of T helper cells (CD4+), has shown significant hyperactivation and participates in kidney damage and many other organs. Th17 cells have IL-17A and IL-17F as main cytokines with receptors expressed in most renal cells, being involved in the activation of many proinflammatory and profibrotic pathways. The Th17/IL-17 axis promotes and maintains repetitive tissue damage and maladaptive repair; leading to fibrosis, loss of organ architecture and function. In the podocytes, the Th17/IL-17 axis effects include changes of the cytoskeleton with increased motility, decreased expression of health proteins, increased oxidative stress, and activation of the inflammasome and caspases resulting in podocytes apoptosis. In renal tubular epithelial cells, the Th17/IL-17 axis promotes the activation of profibrotic pathways such as increased TGF-β expression and EMT promotion with consequent increase of extracellular matrix proteins. In addition, the IL-17 promotes a proinflammatory environment by stimulating the synthesis of inflammatory cytokines by intrinsic renal cells and immune cells, and the synthesis of growth factors and chemokines, which together result in granulopoiesis/myelopoiesis, and further recruitment of immune cells to the kidney. The purpose of this work is to present the prognostic and immunopathologic role of the Th17/IL-17 axis in Kidney diseases, with a special focus on LN, including its exploration as a potential immunotherapeutic target in this complication.